We the People Outside of the Constitution: The Dialogic Model of Constitutionalism and the System of Checks and Balances - Gargarella, Roberto (2014)
All over the world, constitutional theory has been experiencing developments which have been studied under the rubric of dialogic constitutionalism , dialogic justice or dialogic judicial review. These novelties seem to have the capacity to challenge traditional ideas and assumptions concerning the system of separation of powers, the organization of checks and balances, and more particularly judicial review. This article critically assesses the recent development of this dialogic practice through examples mainly coming from Latin America. It maintains that, beside the genuine reasons we have to celebrate the coming of dialogic constitutionalism, we also have reasons for concern, particularly if we are not willing to modify the basic structure of the system of checks and balances on which it is usually based.